2015
DOI: 10.1016/s1473-3099(15)70024-1
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of dose on the antimalarial efficacy of artemether–lumefantrine: a systematic review and pooled analysis of individual patient data

Abstract: SummaryBackground-Artemether-lumefantrine is the most widely used artemisinin-based combination therapy for malaria, although treatment failures occur in some regions. We investigated the effect of dosing strategy on efficacy in a pooled analysis from trials done in a wide range of malariaendemic settings.Methods-We searched PubMed for clinical trials that enrolled and treated patients with artemether-lumefantrine and were published from 1960 to December, 2012. We merged individual patient data from these tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 26 publications
3
41
1
Order By: Relevance
“…This fast action of AL was already reported in studies conducted elsewhere in Ethiopia11,12,20 and Tanzania 24. The emerging resistance to artemisinins on the Thailand–Cambodian border26,27 has been characterized by the slow parasite clearance in vivo and the increased day 3 positive cases 9,12,28,29. The day 3 parasitemia on blood smear is a good predictor of the forthcoming failure in Coartem ® therapy in the areas of low and moderate transmission 9.…”
Section: Discussionsupporting
confidence: 55%
“…This fast action of AL was already reported in studies conducted elsewhere in Ethiopia11,12,20 and Tanzania 24. The emerging resistance to artemisinins on the Thailand–Cambodian border26,27 has been characterized by the slow parasite clearance in vivo and the increased day 3 positive cases 9,12,28,29. The day 3 parasitemia on blood smear is a good predictor of the forthcoming failure in Coartem ® therapy in the areas of low and moderate transmission 9.…”
Section: Discussionsupporting
confidence: 55%
“…However, the WWARN found that the risk of treatment failure with AL was greatest in children underweight-for-age (i.e., suffering from global malnutrition) aged 1–3 years in Africa [18]. In our study, AL was administered concomitantly with RUTF in SAM children, which might have contributed to an improved drug absorption in this group.…”
Section: Discussionmentioning
confidence: 72%
“…Though not correlated with a higher risk of treatment failure or reinfection in our study, the low concentration achieved in SAM and young children is still a concern, as sub-optimal exposure to antimalarials is the first step to the emergence of parasite resistance [35]. The question of adapting dosing strategies in younger and malnourished children should be investigated further [18]. The ongoing PK modelling of our data will include simulation of different AL dosing scenarios to assess their effect on lumefantrine PK profile.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations